Recent Publications (Quarterly Journal of Economics, 1941)
Journal Article Recent Publications Get access The Quarterly Journal of Economics, Volume 55, Issue 4, August 1941, Pages 701–705, https://doi.org/10.1093/qje/55.4.701 Published: 01 August 1941